Assessing concordance of HIV risk behaviors collected by different surveillance systems. (1st October 2022) - Panneer, Nivedha; Balaji, Alexandra B.; Crim, Stacy M.; Bosh, Karin A.; Shouse, R. Luke; Fagan, Jennifer L.; Beer, Linda
Abstract : Objectives: Assess concordance of assigned transmission category between National HIV Surveillance System (NHSS) and Medical Monitoring Project (MMP); assess persistence of behaviors by comparing transmission category to current behavior. Design: Retrospective analysis of HIV surveillance data. Methods: For 4034 participants in the 2016 MMP cycle, transmission category was assigned in NHSS and MMP by applying a hierarchy to acquisition risk behaviors and selecting the most likely risk behavior that led to HIV acquisition. We assessed concordance of transmission category between systems, the number of persons with an updated transmission category in NHSS after incorporating MMP data, and concordance of transmission category and current behavior. Results: Concordance of transmission category between NHSS and MMP was 87% for men with evidence of male-to-male sexual contact and ranged from 27% to 62% in persons with other transmission categories. Transmission category in NHSS was updated for 9% of persons after incorporating MMP data, mostly affecting those with no identified risk in NHSS. Current behavior aligned with updated NHSS transmission category in 56% of men with a transmission category of male-to-male sexual contact. However, only 8% of men and 5% of women with a transmission category of injection drug use had recently injected drugs. Conclusion: HIV surveillance systems can better inform prevention efforts with more complete risk information. Sexual behaviors are more persistent over time than injection drug use. In addition to promoting viral suppression, routinely assessing risk and tailoring prevention activities accordingly can improve health outcomes.